Notes on the distribution and habitat of Ochthebius lobicollis Rey, 1885, a poorly known north-western Mediterranean coastal species (Coleoptera: Hydraenidae) - Ribera, Ignacio; Hernando, Carles (Fragmenta entomologica, 2019)
Ochthebius (Ochthebius) lobiccoastal habitatsollis Rey, 1885 is recorded for the first time from the Iberian Peninsula (Girona) and the island of Corsica; new records are also given for the islands of Menorca and Sardinia. The species is known only from coastal habitats through the Gulf of Lion and the Ligurian and Balearic seas, typically living in rockpools of different salinity or small trickles or freshwater runoffs. Genetic data of the cytochrome oxidase 1 gene from Iberian, Menorcan and Sardinian specimens shows less than 1% divergence, suggesting lack of isolation between populations.